The Camelback Zn-Pb-Cu Deposit: A Recent Discovery in the Bathurst Mining Camp, New Brunswick, Canada - J. A. Walker; J. I. Carroll (Canadian Institute of Mining, Metallurgy and Petroleum, 2006)
"Abstract - Camelback is a small (=200 000 tonnes), moderate grade (5%-7% Zn+Pb), volcanogenic massive sulfide deposit, which occurs within the Nepisiguit Falls Formation of the Ordovician Tetagouche Group. The host rocks are tuffaceous sedimentary rocks (Little Falls member) that overlie quartz-feldspar porphyritic tufflavas (Grand Falls member). The hanging-wall sequence comprises rhyolite of the Flat Landing Brook Formation, overlain by the Forty Mile Brook tholeiitic basalt. A dike of unaltered andesite was intersected beneath the massive sulfides, but was not found in the hanging-wall sequence in the vicinity of the deposit. The stratiform part of the deposit is made up of two, steeply south dipping, subparallel massive lenses that average approximately 4 m in thickness. Each lens is zoned, with an upper part consisting mainly of a pyrite and a basal part containing pyrite, sphalerite, and galena, with Ag values. The Au content in the massive sulfides is low (average = 52 ppb for 271 samples), but tends to be enriched in the massive pyrite near the top of each lens. Oxide facies iron formation is spatially associated with the massive sulfides, and has been traced up to 1800 m along strike. Footwall hydrothermal alteration is typical of VMS systems, and is characterized by depletion in K2O and Na2O, and enrichment in MgO and Fe2O3T with proximity to massive sulfides. The massive lenses are underlain by intensely chloritic, fine-grained, tuffaceous sedimentary rocks containing locally significant sulfide (chalcopyrite > pyrite > pyrrhotite) veins, which are interpreted to represent feeder zone mineralization. Unlike many VMS deposits, there is no evidence of silicification beneath the massive sulfides at the top of the feeder zone. The oxygen isotopic compositions (d18O = -1.5‰ to -0.3‰) of hydrothermal chlorite coupled with sulfur isotopic compositions (d34S ˜ 12‰) of the massive sulfides suggest that seawater was the dominant fluid in the hydrothermal system. Normalized rare earth element diagrams show flat Ce profiles and positive Eu anomalies, indicating that modified seawater was involved in ore formation; i.e., high-temperature (=350ºC), acidic, and reduced prior to entrainment into the hydrothermal cell. Although, seawater was the dominant fluid in the sulfide-forming system, d34S values of stringer zone sulfides (8.5‰) coupled with elevated Sn (400 ppm) in one massive sulfide sample indicate that there was at least some magmatic component in the hydrothermal cell."